HUBUNGAN KUALITAS SEDIAAN BAKTERI TAHAN ASAM (BTA) TERHADAP HASIL DIAGNOSIS PASIEN TUBERKULOSIS PARU - Niken Niken; Ika Yulia Darma; Hendra Yulia (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2022)
ABSTRACT Background:Based on observations, it was found that patients with suspected TB did sputum examination, but saliva samples were given, so that the quality of the smear preparations was poor and caused false negative results. Patients are advised to give a new sample in the form of mucopurulent so that a better AFB preparation is obtained and the actual results are obtained. Methods: This study aims to determine the quality of acid proof bacteria preparations on the results of the diagnosis of pulmonary tuberculosis patients at Yos Sudarso Hospital, Padang. The research design was cross sectional. Samples were sputum samples from 60 patients. Univariate analysis was conducted to see the frequency distribution of each variable. Bivariate analysis is a statistical analysis used to find the relationship between the quality of acid proof bacteria preparations and the diagnosis of pulmonary TB patients at Yos Sudarso Hospital, Padang. This analysis aims to find the relationship between variables with the statistical test of chi square correlation analysis Results:The results of the study stated that the p value was 0.000, which means <0.05, so it was concluded that there was a significant relationship between the quality of acid proof bacteria preparations and the diagnosis of pulmonary tuberculosis patients. Conclusion:The conclusion of the study, the results of the patient's diagnosis were 33 positive for TB, then the best quality of acid proof bacteria preparations was in the dimensions of size and flatness